Case report: Bilateral eye injuries in members of one family due to a cluster munition in Ukraine - Nowomiejska, Katarzyna; Adamczyk, Katarzyna; Haszcz, Dariusz; Preys, Nataliya; Rejdak, Robert (Frontiers in Medicine, 2023)
The aim of the study was to report the effects of surgical treatment of three victims of a cluster munition in Ukraine. A 32-year-old female and her sons - 6-year old male twins presented in Poland after 18 days of delay of treatment. All ocular injuries were bilateral. One of the boys presented with total retinal detachment and a post-traumatic cataract as well as corneal sutures in one eye, and a post-traumatic cataract in the other eye. The other boy had already developed atrophy in one eye and a vitreous hemorrhage in the other eye. Female suffered from bilateral post-traumatic cataract with multiply glass intraocular foreign bodies (IOFBs). The surgical treatment included cataract surgery with intraocular lens implantation implantation in four eyes, removal of IOFBs in two eyes, and enucleation of the atrophic eye with implantation of an ocular prosthesis. Eye with retinal detachment underwent pars plana vitrectomy. The boy with the atrophic eye due to an open-globe injury received an ocular prosthesis preventing constriction of the tissues of the face, the vitreous hemorrhage resolved itself. Postoperatively, visual acuity improved significantly in four of six eyes. Only in the eye with an open-globe injury and persistent retinal detachment, the final visual acuity was still poor. In conclusion, cluster munition may lead to bilateral ocular trauma with IOFBs, open- and close globe injuries and severe vision loss, if left untreated. Modern ophthalmic surgery leads to vision improvement and solving the eyes after severe combat injury.